Socio-Spatial Conditions of Educational Participation: A Typology of Municipalities in the Canton of Zurich - Sybille Bayard; Flavian Imlig; Simona Schmid (MDPI AG, 2022)
The Canton of Zurich is characterized by strong socio-spatial polarization typical for large and dynamic metropolitan areas. A helpful way to depict spatial dimensions is spatial typologies. Existing spatial categorizations of the Canton of Zurich are limited for education because they focus primarily on economic factors, which are not the only predictors of educational behavior and success. In this paper, we develop a typology of municipalities in the Canton of Zurich that is useful for educational analyses and administrative activity. Theoretically, we consider socio-spatial structures as opportunities and constraints of the spatial and social contexts related to educational participation. We differentiate between two levels: socioeconomic composition and regional structures. The socioeconomic composition of a neighborhood is assumed to influence the way residents think and act through social interactions. Regional structures refer to the variation in the specificity and accessibility of institutional settings of the labor market, the education system, and extracurricular stimulation. The analyses are based on official statistics. We use factor analysis to identify the main components within the two levels. Their combination results in a spatial typology consisting of five types. They show significant differences in indicators of educational participation, which illustrates the relevance of the typology for the education sector.